Analisis Penggunaan Media Grafis oleh Guru Mapel Geografi Kelas X SMAN 1 - Utari Hadiningsih; Novita Sariani (Universitas Indraprasta PGRI Jakarta, 2020)
The purpose of this research is to see how the use of graphic media by geography subject teachers in class X SMA Negeri 1 Tanah Pinoh Melawi Regency is applied as well as to get the clarity, and the description about the analysis of the use of graphic media by Geography subject teachers in Class X SMA Negeri 1 Tanah Pinoh, Melawi Regency. This study used a qualitative method with an analytic descriptive approach, that was, the researcher conducted a deeper analysis using graphic media in geography lessons. The subjects in this study were class X students of SMA Negeri 1 Tanah Pinoh, Melawi Regency in the academic year 2019. The results of this study were seen using graphic media for learning geography to increase the proportion to 69.38%, while specifically it could be detailed through the research aspects carried out in research, as follows: the steps for using graphic media can be categorized as “Good” with a percentage of 71.39%, the efforts to use graphic media can be categorized as “Good” with a percentage of 71.76%, and the constraints on the use of graphic media can be categorized as “good” with a percentage of 50.69%.